2020
DOI: 10.1007/s11469-019-00210-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Mukbang Addiction Scale

Abstract: Recent literature has speculated that some individuals spend lots of time watching mukbang (i.e., combination of the South Korean words 'eating' ['meokneun'] and 'broadcast' ['bangsong'] that refers to eating broadcasts where a person eats a large portion of food on camera whilst interacting with viewers) and compensate different needs using this activity. However, compensating unattained offline needs using a specific online activity could lead to the addictive use of that activity. The present study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 35 publications
3
44
0
2
Order By: Relevance
“…The reliability coefficient of the MAS was excellent (0.95) in the original study. 26 The CRS coefficient was also excellent in the present study (α=0.92).…”
Section: Mukbang Addiction Scale (Mas 26 )supporting
confidence: 74%
See 2 more Smart Citations
“…The reliability coefficient of the MAS was excellent (0.95) in the original study. 26 The CRS coefficient was also excellent in the present study (α=0.92).…”
Section: Mukbang Addiction Scale (Mas 26 )supporting
confidence: 74%
“…To date, there is only one study investigated problematic mukbang watching via examining different profiles of this behavior. 26 The authors concluded that a minority of the participants could be labelled as high endorsement group (i.e., problematic mukbang watchers).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mukbang Addiction Scale (MAS): The MAS (Kircaburun et al 2020b) was used to assess problematic mukbang watching (e.g., "How often during the last year have you felt an urge to watch mukbang more and more?"). The initial validation study indicated mostly sound psychometric properties for unidimensional structure (χ 2 /df = 2.42, RMSEA = 0.08 (CI 90% (0.03, 0.13)), SRMR = 0.01, CFI = 0.99, GFI = 0.98).…”
Section: Methodsmentioning
confidence: 99%
“…From this perspective, obtaining aforementioned gratifications by watching mukbang (i.e., social reasons, entertainment reasons, escapist reasons, virtual eating reasons) may transform recreational mukbang watching into excessive and problematic (i.e., potentially addictive) activity for some viewers. To date, only one crosssectional study has provided any empirical evidence for problematic mukbang watching by showing that some individuals might demonstrate addiction-like symptoms associated with their mukbang watching (i.e., salience, tolerance, relapse, conflict, mood modification, withdrawal), and that the frequency of daily time spent watching mukbang was moderately related to problematic mukbang watching (Kircaburun et al 2020b).…”
mentioning
confidence: 99%